Targeting inflation: The effects of monetary policy on the CPI and its housing component - Dimitri B. Papadimitriou; L. Randall Wray (Levy Economics Institute of Bard College, 1996)
The targets for monetary policy adopted by the Fed in recent years have not proven to be closely correlated with inflation, leading some theorists and policymakers to advocate the use of a price index, such as the consumer price index (CPI), as both the target and the goal of monetary policy. The authors of this brief show that such a choice is not wise because the CPI does not accurately reflect market-caused price increases and is not under the control of monetary policy. Their analysis extends beyond that of recent reports to show how and why the transmission mechanisms through which monetary policy is thought to affect the CPI are tenuous at best. The authors focus on the housing component of the CPI to illustrate their point. They conclude that those components of the CPI that monetary policy is likely to affect have been declining in importance, meaning that to produce a given reduction in the overall rate of inflation will require that monetary policy have an increasingly larger impact on an ever-diminishing portion of the consumer basket. Therefore, careful reconsideration of an alternative ultimate target, such as the rate of economic growth or the unemployment rate, is warranted.
Keywords: 330